Riccardo Martin (1879-1952), American tenor (Tufts Archival Research Center, 2015)
Inscription on front reads: "To Henry Y. Porter in friendly remembrance of New York 1924 Riccardo Martin." Inscription on back reads" Riccardo Martin, 1879-1952, American Tenor formerly with Metropolitan and Chicago Opera cos."